Biological chemistry: [manual] - Aleksandrova, K. V.; Romanenko, М. І.; Krisanova, N. V.; Ivanchenko, D. G.; Rudko, N. P.; Levich, S. V.; Александрова, Катерина Вячеславівна; Романенко, Микола Іванович; Крісанова, Наталія Вікторівна; Іванченко, Дмитро Григорович; Рудько, Наталія Петрівна; Левіч, Сергій Вадимович (Zaporozhye state medical university, 2017)
This manual is recommended for II year students of International Faculty of specialty "General medicine" studying biological chemistry, as additional material to prepare for practical training semantic modules 6, 7 of module 2 and licensing exam "KROK 1: General medical training".